Assessment of prevalence and risk factors of isolated coronary artery ectasia: A 5-year double-center retrospective study in Yazd, Iran - Hossein Nough; Fatemeh Moradi; Hamid Reza Varastehravan; Leila Afkhami; Marzieh Azimi zade; Hamid Reza Mohammadi; mohammad shafiee; Mahmood Emami Meybodi; Naser Hossein Sartipzade; Farzan SafiDahaj; Arman Nough (Babol University of Medical Sciences, 2024)
Background: The prevalence of Coronary artery ectasia (CAE) varies from 0.‌3 to 5% in different countries. The prevalence of CAE has varied in different parts of the world and the study of risk factors can be effective in the process of diagnosis and treatment of patients, we reviewed patients who underwent coronary angiography for 5 years to determine the prevalence of isolated CAE and its associated risk factors. Methods: A retrospective analysis was conducted on 16600 patients who underwent coronary angiography at Shahid Sadoughi and Afshar hospitals between March 2015 to April 2020. Diagnosis and confirmation of CAE was defined as a vessel diameter greater than 1.5 times the normal diameter of the vessel, which must be confirmed by at least two cardiologists. Demographic variables, angiography and echocardiography reports were included in our final analysis. Results: Isolated CAE was diagnosed in 287 (1.7%) patients. After triple-vessel disease (53%), the left anterior descending artery (LAD) was the commonest affected vessel by ectasia 16% (46 cases). Diffuse isolated CAE was diagnosed in 52% of LAD, 76.6% of Right coronary artery (RCA), and 74.1% of left circumflex artery. A significant association was seen between the vessel involved and the nature of ectasia (p<0.001). Conclusion: In our study, the occurrence of isolated CAE was similar to other studies. This condition often affects all three major vessels of the coronary arteries, and is commonly categorized as type 1, which involves diffuse involvement of the arteries based on the Markis and Harikrishnan Classification.